Registration of 'Julie' High β‐Glucan Spring Barley. Issue 1 (16th October 2012) - Obert, D. E.; Hang, A.; Hu, G.; Burton, C.; Satterfield, K.; Evans, C. P.; Marshall, J. M.; Jackson, E. W.
Abstract : The numerous health benefits associated with the consumption of barley has resulted in U.S. Food and Drug Administration approval for the use of high β‐glucan barley in reducing the risk of cardiovascular disease. With the objective of releasing high‐value food barley to meet that health claim, 'Julie' (Reg. No. CV‐351, PI 665006), a two‐rowed, spring, high β‐glucan barley ( Hordeum vulgare L.) was developed and submitted for release in 2009 by the USDA‐ARS, Aberdeen, ID, in cooperation with the University of Idaho Agricultural Experiment Station. Julie is a selection from the cross 10/'Azhul'//'CDC Alamo'. 10 is a selection from composite cross XXXII made by Dr. Tom Ramage (USDA‐ARS, retired). Azhul is a six‐rowed, high β‐glucan cultivar released by the USDA‐ARS and the Arizona Agricultural Experiment Station and is the progenitor of most high β‐glucan cultivars and germplasm. Azhul was developed by the mutation of line 76‐19‐7 with diethyl sulfate. Line 76‐19‐7 has the pedigree CCXXXII/'Arimont'//'Westbar'. CDC Alamo, tested as HB340, has the pedigree SB85750/Azhul. Under dryland and irrigated conditions, the yield and test weight of Julie are greater than those of the currently grown high β‐glucan varieties CDC Alamo and Azhul, and Julie has a higher yield of barley β‐glucan on a per hectare basis.